Como entendemos a matemática ensinada nos anos inciais? Com a palavra os licenciandos em matemática - Bemme, Luis Sebastiao Barbosa (2015)
This study is part of the line of research ―Formation, Knowledge, and Professional Development‖ of the Graduate Program in Education at Federal University at Santa Maria (UFSM) and presents as main objective to investigate the ways students from the Math Teaching Major at UFSM, who are carrying out their supervised practice, understand the Math subject studied in early years of Elementary School. Data collection in the study was organized in three different moments. The first one concerns the bibliographical research developed along four national events. The second moment was the organization of a questionnaire composed of 16 questions, with the purpose of generally identifying the way Math teachers-to-be understand their initial formation. Finally, the third moment was the organization of a formative space where we tried to discuss the construction of the concept of number and its operations by means of Teaching Guiding Activities. The organization of actions and data analysis were performed under the light of Historical-Cultural Theory, Activity Theory and Teaching Guiding Activity; by using the idea of episodes proposed by Moura (2004). The results indicate that the teachers-to-be acknowledge the importance of Mathematics taught in early years of education, although they are not very clear on how the organization of the discipline occurs in this stage. They also acknowledge that the pedagogue s work is not an easy task and demonstrate to be concerned and aware that, in early years, education demands well-prepared professionals to develop the teacher s work. As considerations on the study, we point out the importance for Math teachers-to-be who will act in the final years of Elementary School and in High School to become closely connected to Mathematics of early years, in terms of teaching organization as well as contents. Besides that, we point out the limited relations among disciplines in the initial formation course and the lack of space so that the teachers-to-be can discuss their own formation. The lack of relations between disciplines called specific and the ones called pedagogic results in the teacher-to-be experiencing two distinct courses, missing necessary connections in the moment of planning actions to be developed in early years. Another issue we highlight is the fact that the initial formation course does not provide the teacher-to-be with the tools needed to the development of teaching in Basic Education. In other words, after graduating the teacher may not have subsidy to think a differentiated teaching that allows students to articulate Math concepts. We also point out that the constitution of a formative space allows the teachers-to-be to reflect on different ways of organizing teaching so that they attribute a new quality to early years.